2019
DOI: 10.5851/kosfa.2019.e16
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Bacterial Communities of Lamb Meat Packaged in Air and Vacuum Pouch during Chilled Storage

Abstract: In this study, the changes in microbial communities of lamb meat packaged in the air (plastic tray, PT) and in a vacuum pouch (VAC) were assessed by polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) during the storage at 4°C. For the PT lamb, the total viable count (TVC) was 10 7 CFU/g on Day 5, and the dominated bacteria were Pseudomonas fragi , P. fluorescens , and Acinetobacter spp. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Meats with bacterial counts higher than 7 log CFU are considered spoilt by the International Commission on Microbiological Specifications for Foods ( ICMSF, 1986 ). Wang et al. (2019) reported that microorganisms can spread easily within chicken flocks stocked at high densities and that bacteria found in chicken carcasses originate from feces or the environment, which contaminate chicken meat and skin during processing in slaughter houses.…”
Section: Resultsmentioning
confidence: 99%
“…Meats with bacterial counts higher than 7 log CFU are considered spoilt by the International Commission on Microbiological Specifications for Foods ( ICMSF, 1986 ). Wang et al. (2019) reported that microorganisms can spread easily within chicken flocks stocked at high densities and that bacteria found in chicken carcasses originate from feces or the environment, which contaminate chicken meat and skin during processing in slaughter houses.…”
Section: Resultsmentioning
confidence: 99%
“…1). By contrast, the mesophiles level determined by Wang et al (2019) in VP lamb meat on the third day of storage was much higher at 4.95 log CFU/g despite the comparable storage temperature of 4− 6 • C.…”
Section: Resultsmentioning
confidence: 77%
“…and Pseudomonas spp. were found to be among the predominant bacteria in lamb meat (Wang et al, 2019). Ahmed and Sabiel.…”
Section: Discussionmentioning
confidence: 96%